Merdeka curriculum: use of information and communication technology media in early childhood education - Ririn Hunafa Lestari; Sharina Munggaraning Westhisi; Liza Bunga Aprilia (IKIP Siliwangi, 2024)
This research aims to determine the use of ICT media in the independent curriculum in early childhood education. To find out this goal, a qualitative descriptive research method was used on the action plans of three professional teacher education students involving an independent curriculum and information and communication technology media based on the observation process and analyzed using grounded theory analysis. Based on the results of the research analysis, the results obtained show that an independent curriculum involves information and communication technology as a learning medium. This is based on the use of ICT in online learning. However, its use is not given directly to children but is regulated by the teacher in planning, implementing, and assessing learning, giving rise to a new approach that can be applied to early childhood education, namely the TPACK learning approach. The TPACK learning approach is a learning approach that involves teacher competence, technology, and learning materials.